IMPLEMENTATION OF EFFORTS TO REDUCE MENSTRUAL PAIN-INCREASE PRODUCTIVITY WITH INTERMITTENT FASTING (16:8) USING THE "GUIDE ME" ANDROID APPLICATION FOR YOUNG WOMEN AT ISLAMIC BOARDING SCHOOL YATIM CAHAYA MADINAH, SOUTH TANGERANG, BANTEN - Desmawati, Desmawati; Ismail, Rita; Noer, Sirajudin; Sudiharto, Sudiharto; Faradillah, Kiki Rezki (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
A common complaint often experienced by adolescent girls during menstruation is menstrual pain or dysmenorrhea. Menstrual pain is caused by an imbalance of hormones such as prostaglandins and progesterone due to uterine contractions that affect each individual. Many activities of adolescent girls are disrupted by this menstrual pain, including female students at the Pesantren Yatim Cahaya Mandiri, South Tangerang, Banten. The objective of this community service is to address menstrual pain in adolescents through several methods including: 1) providing education on nonpharmacological therapy to reduce menstrual pain, addressing the lack of information, knowledge, and understanding related to menstruation; 2) training in life skills to adapt to menstrual disturbances, aimed at overcoming the low level of life skills in dealing with menstrual issues; 3) implementing 16-hour Intermittent Fasting (16:8) and doing murojaah (to maintain the memorization of the Quran good, fluent, and correct) using the "Guide Me" app for menstrual pain in adolescent girls; 4) supervising and reevaluating programs to address menstrual disturbances using the "Guide Me" app; 5) adopting positive lifestyle changes to reduce menstrual disturbances (efforts to reduce menstrual pain). Adolescents are able to remain productive during menstruation, implement Intermittent Fasting (16:8), and stay healthier and more productive even while menstruating. The results of this intervention have proven effective in reducing menstrual pain through non-pharmacological therapy, leading to healthier and more sustainable productivity for adolescent girls. Those who initially experienced severe pain (scale 6), causing distress and lower abdominal cramps during menstruation that often reduced their quality of life—along with discomfort affecting their physical and mental well-being, often accompanied by nausea, vomiting, abdominal pain, breast pain, rectal swelling, and diarrhea—reported a reduction in menstrual pain to a scale of 3 after this intervention.